From Culture to Science: An Analysis of Ethnoscience Integration in Pre-Service Physics Teachers’ Lesson Plans - Linda Dwi Astuti; Aulia Silvina Anandita; Fairusy Fitria Haryani (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
The integration of local wisdom in science learning is important to create contextual and meaningful learning experiences. However, prospective teachers often experience difficulties in systematically integrating ethnoscience elements into learning design. This study aims to examine the integration of local wisdom in ethnoscience-based learning designs developed by physics education students. This study employed a qualitative descriptive approach through document analysis of eight lesson plans. Data were analyzed using content analysis using an assessment rubric covering five aspects: (1) learning objectives, (2) learning activities, (3) ethnoscience context integration, (4) learning strategies, and (5) learning assessment planning. The results showed that the quality of the lesson plans ranged from fair to very good. The highest scores were found in ethnoscience integration, while the lowest were in learning assessment planning. Students were generally able to relate cultural practices to scientific concepts contextually, although the depth of integration and consistency in learning strategies varied. Some lesson plans developed experience-based learning activities, while others only used cultural contexts as illustrations. These findings indicate the need to strengthen conceptual elaboration, exploratory learning strategies, and assessment design to support effective ethnoscience integration in learning design